Analisis Hubungan Dana Transfer ke Daerah dan Belanja Pegawai terhadap Kualitas Penyelenggaraan Urusan Publik di Kabupaten Kediri - Muhammad Reza Zakaria; Adyakzada Reswara Prambudi; Revienda Anita Fitrie; Eva Hany Fanida (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The quality of public service delivery serves as a benchmark for the success of decentralization in Indonesia. This study aims to analyze the influence of Regional Transfer Funds (TKD) and Personnel Expenditures on the quality of public service delivery in Kediri Regency for the 2020–2025 period, both partially and simultaneously. The method used is quantitative research with an associative (causal) approach. The data are secondary in nature, consisting of time-series data sourced from the Budget Implementation Report (LRA) of the Kediri Regency APBD via the DJPK portal of the Indonesian Ministry of Finance, as well as Human Development Index (HDI) data from the Central Statistics Agency (BPS) of Kediri Regency as a proxy for the quality of public service delivery. The analysis results indicate that Regional Transfer Funds do not have a significant or direct impact on HDI improvement, as fluctuations in the amount of transfers are not accompanied by proportional changes in the HDI. Personnel Expenditures, which on average account for more than 40% of operating expenditures, also do not significantly affect service quality, as evidenced by the rise in the HDI in 2023 when personnel expenditure realization was actually at its lowest point. Simultaneously, these two variables have not been able to create optimal leverage for the quality of public affairs. These findings underscore the importance of reforming the structure of local government spending to be oriented toward public value and strengthening performance-based transfer mechanisms.